Solve for n (-6+n)/10=-2

Math
-6+n10=-2
Multiply both sides of the equation by 10.
10⋅-6+n10=10⋅-2
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 10.
Tap for more steps…
Cancel the common factor.
10⋅-6+n10=10⋅-2
Rewrite the expression.
-6+n=10⋅-2
-6+n=10⋅-2
Multiply 10 by -2.
-6+n=-20
-6+n=-20
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 6 to both sides of the equation.
n=-20+6
Add -20 and 6.
n=-14
n=-14
Solve for n (-6+n)/10=-2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top